Role of the quorum sensing mechanism in the response of pseudomonas aeruginosa to lethal and sublethal UVA irradiation - Costa, Cristina Susana (2010)
The role of quorum sensing (QS) in the response of Pseudomonas aeruginosa to UVA radiation was investigated in the PAO1 strain and derivatives defective in the synthesis of the QS signals 3OC12-HSL (lasI strain), C4-HSL (rhlI strain) or both (lasI rhlI strain). Cell viability measurements demonstrated that the double mutant was significantly more sensitive to UVA than single mutants, which in turn showed reduced cell survival with regard to the PAO1 strain. Irradiation under nitrogen atmosphere and chemiluminescence measurements indicated the oxidative nature of the UVA-induced damage. The activity of the antioxidant enzymes catalase and superoxide dismutase was assayed in these strains before and after irradiation, and a strong correlation between catalase levels and UVA sensitivity was observed. When a sublethal UVA dose was applied to PAO1, a growth delay was observed and this mechanism depended on the rhl system. Moreover, low doses of UVA irradiation triplicated the level of C4-HSL in log PAO1 cells. It is concluded that QS is fundamental in the defense against the toxic effects of UVA in P. aeruginosa. The induction of the QS system by UVA independently of cell density could function as an adaptative strategy to withstand this hostile environmental condition.